PENGARUH PENAMBAHAN INOKULUM, LAMA FERMENTASI DAN PENGADUKAN PADA PEMBUATAN VIRGIN COCONUT OIL (VCO) MENGGUNAKAN KHAMIR SACCHAROMYCES CEREVISIAE MURNI - Jernika Simangunsong, Elisa Febrina, Zuhrina Masyithah (Universitas Sumatera Utara, 2016)
Virgin coconut oil (VCO) is coconut oil that processed without heating. This study about fermentation of VCO using Saccharomyces cerevisiae. The purposes of this research is to find the best condition like stirring times, stirring speeds, fermentation times and concentration of inoculum in the process of making VCO. The variation of stirring speeds are 25 rpm, 50 rpm, 75 rpm, 100 rpm and 125 rpm. Stirring time used was 15 minutes, 30 minutes, 45 minutes, 60 minutes and 75 minutes. The variation of fermentation times are 6 hours, 12 hours, 18 hours, 24 hours, and 30 hours and variation concentration of inoculum are 5%, 10%, 15%, 20% and 25%. For stirring effects, the highest yield was obtained 24,5% with stirring speed is 50 rpm and stirring time is 30 minutes and the lowest yield was obtained 8,5% with stirring speed is100 rpm and stirring time 75 minutes. For fermentation times and concentration inoculum effets, the highest yield was obtained from this research is 28,25% with addition inoculum is 10% and fermentation times is 24 hours. And the lowest yield is 15% with addition inoculum is 20% and fermentation times is 12 hours. The results of this research for stirring effects showed decreases yield of VCO and for the fermentation time showed increases yield of VCO and concentration inoculum showed no effect for yield of VCO.